Das biharmonische Integral von Poisson - Petrov, V. V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: B. А. Петров. Бигармонический интеграл Пуассона V. Petrovas. Biharmoninis Puasono integralas